6p+3-2p=27

Simple and best practice solution for 6p+3-2p=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+3-2p=27 equation:


Simplifying
6p + 3 + -2p = 27

Reorder the terms:
3 + 6p + -2p = 27

Combine like terms: 6p + -2p = 4p
3 + 4p = 27

Solving
3 + 4p = 27

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 4p = 27 + -3

Combine like terms: 3 + -3 = 0
0 + 4p = 27 + -3
4p = 27 + -3

Combine like terms: 27 + -3 = 24
4p = 24

Divide each side by '4'.
p = 6

Simplifying
p = 6

See similar equations:

| k-10=5+4k | | 8x^2+33x-4=0 | | 0.75x=1 | | 4x-7(32+7)=2x+15 | | 3(2y+7)=-18 | | 4y^2-25x^2=0 | | 2b+10=3b | | 1/16^-3/2 | | 2/3x+6 | | 36t+9=27t | | 4(x+3)+2x=x-84 | | 4(3y+5)+2(6y+1)=94 | | 1.5(4x+3)=8x-9.5 | | 8+4x-2=5x+3x+6 | | 180=(x+3)*(2x+4) | | 2f+13=5f-8 | | 180=3x^2+10x+12 | | -2(36)-y=-9 | | 7x-26=58 | | -10-10x=7x+254 | | -5(-0.33)-8y=17 | | 2x-7(2.125-0.625x)=-17 | | 2(x-3)=14-3x | | (17-5x)/3=x | | (17-5x)=x | | 54x^2+x^4=1120 | | 6x+10-x-15x+15x= | | 2x+13=63-2x | | -7(-3+3y)+8y=-5 | | 6x+26=16x-24 | | -3x-4(-1-1x)=2 | | 2(-28)+y=20 |

Equations solver categories